Perimenopause and Postmenopause – Diagnosis and Interventions. Guideline of the DGGG and OEGGG (S3-Level, AWMF Registry Number 015-062, September 2020) - Inwald, Elisabeth C.; Albring, Christian; Baum, Erika; Beckermann, Maria; Bühling, Kai J.; Emons, Günter; Gudermann, Thomas; Hadji, Peyman; Imthurn, Bruno; Kiesel, Ludwig; Klemperer, David; Klose, Petra; König, Klaus; Krüger, Stephanie; Langhorst, Jost; Leitzmann, Michael; Ludolph, Albert; Lüftner, Diana; Müller, Dorothea; Neulen, Joseph; Nothacker, Monika; Eckhard Petri †; Prautzsch, Horst; Regitz-Zagrosek, Vera; Schaudig, Kathrin; Schütz, Florian; Schwenkhagen, Anneliese; Strowitzki, Thomas; Stute, Petra; Taute, Bettina-Maria; Tempfer, Clemens; Arnim, Christine v.; Wildt, Ludwig; Windler, Eberhard; Ortmann, Olaf (Geburtshilfe und Frauenheilkunde, 2021)
Aim The aim of the interdisciplinary S3-guideline Perimenopause and Postmenopause – Diagnosis and Interventions is to provide help to physicians as they inform women about the physiological changes which occur at this stage of life and the treatment options. The guideline should serve as a basis for decisions taken during routine medical care. This short version lists the statements and recommendations given in the long version of the guideline together with the evidence levels, the level of recommendation, and the strength of consensus.Methods The statements and recommendations are largely based on methodologically high-quality publications. The literature was evaluated by experts and mandate holders using evidence-based medicine (EbM) criteria. The search for evidence was carried out by the Essen Research Institute for Medical Management (EsFoMed). To some extent, this guideline also draws on an evaluation of the evidence used in the NICE guideline on Menopause and the S3-guidelines of the AWMF and has adapted parts of these guidelines.Recommendations Recommendations are given for the following subjects: diagnosis and therapeutic interventions for perimenopausal and postmenopausal women, urogynecology, cardiovascular disease, osteoporosis, dementia, depression, mood swings, hormone therapy and cancer risk, as well as primary ovarian insufficiency.Ziel Ziel der interdisziplinären S3-Leitlinie „Peri- und Postmenopause – Diagnostik und Interventionen“ ist es, Ärzte bei der Aufklärung von Frauen über die physiologischen Veränderungen in dieser Lebensphase sowie Therapiemöglichkeiten zu unterstützen. Die Leitlinie soll eine Entscheidungsgrundlage im ärztlichen Alltag darstellen. In der vorliegenden Kurzversion werden die Statements und Empfehlungen der Langversion mit Evidenzgrad, Empfehlungsgrad und Konsensusstärke aufgeführt.Methoden Die Statements und Empfehlungen basieren überwiegend auf methodisch hochwertigen Publikationen. Es erfolgte eine Bewertung der Literatur nach den Kriterien der evidenzbasierten Medizin (EbM) durch Experten und Mandatsträger. Die Evidenzrecherchen wurden vom Essener Forschungsinstitut für Medizinmanagement GmbH (EsFoMed) durchgeführt. Teilweise wurde auf die Evidenzbewertung der NICE-Guideline Menopause und S3-Leitlinien der AWMF im Sinne einer Leitlinienadaptation zurückgegriffen.Empfehlungen Es werden Empfehlungen zu folgenden Themen gegeben: Diagnostik und therapeutische Interventionen bei peri- und postmenopausalen Frauen, Urogynäkologie, kardiovaskuläre Erkrankungen, Osteoporose, Demenz, Depression, Stimmungsschwankungen, Hormontherapie und Krebsrisiko sowie prämature Ovarialinsuffizienz.
Keywords: perimenopause; postmenopause; hormone (replacement) therapy; diagnosis; therapy; cancer risk; guideline